ANALISIS KECERDASAN KOGNITIF PESERTA DIDIK DALAM PEMBELAJARAN SKI DI MTs BAITUL AZIZ - Wiwik Dyah Aryani; Bunga Ayu Lavenia; Asep Muhammad Irfan Hilmi; Wilda Solihat (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze students' cognitive intelligence and its influence on the understanding of Islamic Cultural History (SKI) subject material at MTs Baitul Aziz. The background of this research lies in the phenomenon where many students show differences in comprehension levels when dealing with SKI material that demands high cognitive abilities, such as analyzing historical events, connecting historical facts, and drawing conclusions from Islamic civilization. This study employed a qualitative descriptive approach with data collection techniques including observation, interviews, documentation, and cognitive tests. The subjects of this study were students of class VII, VIII, and IX at MTs Baitul Aziz. The results showed that students with high cognitive intelligence tend to demonstrate deeper understanding of SKI material, are more capable of analyzing historical relationships, and show higher critical thinking skills. Meanwhile, students with moderate and low cognitive intelligence require more intensive scaffolding strategies and more contextual learning approaches. This study also found that the use of active learning strategies such as Socratic discussion, historical mapping, and thematic storytelling can significantly improve the cognitive understanding of all students regardless of their initial cognitive level. These findings suggest the need for differentiated learning approaches in SKI to accommodate the diversity of students' cognitive intelligence levels optimally.